2012
DOI: 10.1371/journal.pone.0042809
|View full text |Cite
|
Sign up to set email alerts
|

High-to-Low CO2 Acclimation Reveals Plasticity of the Photorespiratory Pathway and Indicates Regulatory Links to Cellular Metabolism of Arabidopsis

Abstract: BackgroundPhotorespiratory carbon metabolism was long considered as an essentially closed and nonregulated pathway with little interaction to other metabolic routes except nitrogen metabolism and respiration. Most mutants of this pathway cannot survive in ambient air and require CO2-enriched air for normal growth. Several studies indicate that this CO2 requirement is very different for individual mutants, suggesting a higher plasticity and more interaction of photorespiratory metabolism as generally thought. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
141
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(154 citation statements)
references
References 81 publications
12
141
1
Order By: Relevance
“…Furthermore, these changes were not persistent over the whole analyzed period and appeared solely at one or two specific time points (Supplemental Table S2). Moreover, if compared with the strong alterations observed with other photorespiratory mutants Voll et al, 2006;Engel et al, 2007;Collakova et al, 2008;Timm et al, 2012b;Eisenhut et al, 2013), these metabolic changes are of a very moderate character, confirming the suitability of hpr1 as a model to study the direct feedback of a slightly and specifically reduced internal carbon flow on the regulation of photorespiration.…”
Section: Deletion Of Hpr1 Changed the Accumulation Pattern For Sermentioning
confidence: 52%
See 3 more Smart Citations
“…Furthermore, these changes were not persistent over the whole analyzed period and appeared solely at one or two specific time points (Supplemental Table S2). Moreover, if compared with the strong alterations observed with other photorespiratory mutants Voll et al, 2006;Engel et al, 2007;Collakova et al, 2008;Timm et al, 2012b;Eisenhut et al, 2013), these metabolic changes are of a very moderate character, confirming the suitability of hpr1 as a model to study the direct feedback of a slightly and specifically reduced internal carbon flow on the regulation of photorespiration.…”
Section: Deletion Of Hpr1 Changed the Accumulation Pattern For Sermentioning
confidence: 52%
“…First, after Gly supplementation of Arabidopsis seedlings, the internal concentration of this amino acid is reduced to one-half of that found in nontreated seedlings. Second, the accumulation of Gly in hpr1 during the high-to-low CO 2 transition after 1 d is less distinct 3 d after transfer to normal air (Timm et al, 2012b). Both findings indicate that Gly could act as a transcriptional inductor for GDC proteins to adapt plants for photorespiratory conditions.…”
Section: Ser Rather Than Gly As a Possible Metabolic Signal For The Tmentioning
confidence: 89%
See 2 more Smart Citations
“…12,13 In addition, a role of Ser or Ser derivatives (D-Ser) in a plant signaling mechanism or in regulating transcripcional and translational networks should also be taken into account. 3,14 Finally, it could be argued that PSP1 performs additional functions, as has been demonstrated for other metabolic enzymes in plants. Along these lines, Bachelor et al (2011) 17 found that PSP1 overexpression in mammal cells abrogates squamous cell carcinoma proliferation independently of serine levels, thus postulating additional roles for the enzyme, such as additional enzymatic substrates or novel non-enzymatic interacting proteins, which may be important for carcinogenesis.…”
mentioning
confidence: 85%